Positioning Ideologi Partai Politik Dalam Pembentukan Koalisi Indonesia Adil Makmur Pada Pemilihan Presiden Tahun 2019 - Hermanto, Bambang (Jurnal Transformative, 2019)
This article analyzes the ideological positioning of political parties in the formation of the Indonesia Adil Makmur Coalition in the 2019 Presidential Election. Democracy has brought political parties in the political electoral. In 2014 the dynamics of political parties in Indonesia before and after the Presidential Election were interpreted as manifestations of the office-seeking coalition model. The characteristics of the office-seeking coalition model are fluid and not permanent. This seems to justify a practical political adage which states that in politics there are no eternal friends or enemies, what is in the interests of servants. The 20% presidential threshold has resulted in political parties having to form coalitions to support candidates in the Presidential Election in 2019. The method used in this study is media analysis and literature studies. The results of the analysis indicate that the coalition of political parties in the 2019 Presidential Election is a must for political parties. The emergence of the catch-all party shows pragmatism and shifts the ideology of political parties in building the coalition. This proves the lack of commitment and weakening of the ideology of political parties from time to time. Political parties focus more on getting a share of power. From the explanation above, it can be concluded that ideology cannot be used as the absolute preference of the coalition of political parties. Because it is proven that the composition of the coalition is not always formed on the basis of ideology. This explains that the formation of coalitions is the basis of political interests that are non-ideological or office-seeking to get a share of power.